I feel wealthy: a major determinant of Portuguese households' indebtedness? - Vale, S.; Camões, F. (14th EBES Conference - Barcelona Program and Abstract Book, 2014)
In this paper we investigate the features of Portuguese households that hold debt and how Portuguese households' indebtedness can be related to macroeconomic fundamentals, namely the high valuation of the housing sector that occurred in the last decades. Using data from the first wave of the Household Finance and Consumption Survey we estimate a logit model for the probability of holding debt controlling for households' economic and socio-demographic characteristics, adverse changes, and pessimistic and optimist expectations, and taking into account the perception of wealth accumulation that emerged from the strong price surge in the housing sector. Additionally, we estimate the probability of holding mortgage debt, any other type of debt, and of holding excessive debt levels by using standard literature criteria for the definition of over-indebtedness. Our results indicate that a wealth perception effect is particularly evident in the probability of contracting non-mortgage debt, but that this effect is mitigated in the probability of holding mortgage debt and in the probability of incurring an excessive debt burden.